EFFECT OF TEMPERATURE VARIATION ON THE PRODUCTION OF BIODIESEL USING NEEM OIL - Ahmed Lira, Mujidatu; Idris Atadash, Musa (International Journal of Research -GRANTHAALAYAH, 2018)
Biodiesel was produced from neem seed oil via a two-step process of esterification and transesterififcation reactions. The transesterification was carried out using CH3ONa as catalyst with ethanol as the alcohol. The reaction temperature was varied between 30, 40, 50, 60, and 700C, while all other process parameters were kept constant. From the results obtained, a significant change in biodiesel yield (73-79%) from 30-50oC temperatures was observed. At a temperature of 60oC, a good yield of 94% was obtained which was observed at a temperature below the boiling point of the alcohol used. At 70oC biodiesel yield of 67% was obtained; this indicates a drop in biodiesel yield. Further flash point of 149.60C indicated that the biodiesel produced is within the specification of ASTM D6751. Also, the high value of flash point indicated that the fuel is safe for handling as it exceeds the minimun ASTM requirement (130min). It is worthy to mention that other properties such as viscosity, pour point and cloud point etc investigated also presented good values which were within ASTM D6751. The formation of biodiesel was confirmed by FT-IR analysis. The conversion of the ester functional group into methyl esters in biodiesel verified the success of the reaction.